2022
DOI: 10.19164/ijgsl.v2i1.1259
|View full text |Cite
|
Sign up to set email alerts
|

Webcam Performers Resisting Social Harms: “You're on the Web Masturbating… It's Just about Minimising the Footprint”

Abstract: This article will bring together Deleuze and Guattari’s theory of Smooth Space and zemiological debates of social harms to respond to the question set by Jane Scoular (2015): does the law matter in sex work? The regulation and policing of performers by hosting sites allow sites to avoid state-level legislation. However, site regulations cause performers to experience harm that traditional concepts of the law cannot address because the law is powerless against the intrinsic injuries done by neo-liberalism. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Again, not just users but platforms play a role here as well. As previous research has demonstrated, some webcam platforms record and resell content for profit (Stuart, 2022).…”
Section: Experiences Of Involuntary Hypervisibilitymentioning
confidence: 92%
See 1 more Smart Citation
“…Again, not just users but platforms play a role here as well. As previous research has demonstrated, some webcam platforms record and resell content for profit (Stuart, 2022).…”
Section: Experiences Of Involuntary Hypervisibilitymentioning
confidence: 92%
“…This is precisely what prevents Mihaela*, a Romanian webcam performer, from growing her audience too much, “I don’t wish to get really popular, I don’t want people to share my posts too much, or I don’t know if they screenshot, record videos, or whatever, or link to my page.” Again, not just users but platforms play a role here as well. As previous research has demonstrated, some webcam platforms record and resell content for profit (Stuart, 2022).…”
Section: Experiences Of Involuntary Hypervisibilitymentioning
confidence: 98%
“…Like algorithms more generally, studies show how such affordances uphold white supremacy, which (inadvertently) tends to reinforce white heteropatriarchal beauty standards (Glatt, 2022; Jones, 2015). Research has paid attention to how capitalist companies, such as adult platforms, are shaping and benefitting from some sex workers' move online (Stuart, 2022, p.189). They have a vested interest in maximizing their profits, and their technological designs reflect this, not the needs of workers.…”
Section: Platform Affordances In Digital Labormentioning
confidence: 99%
“…Sex work is no exception to the larger trend of platformization. Webcamming, a popular type of sex work (Sanders et al, (Jones, 2020;Nayar, 2017;Stuart, 2022). However, ranking systems can vary significantly, calling for studies that compare them across multiple platforms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, their presence on the platform needs to be taken into account. Finally, existing research on webcamming often focuses on a single platform (Hernández, 2019; Jones, 2015; van Doorn & Velthuis, 2018; Velthuis & van Doorn, 2020), a specific geographic location (Caminhas, 2022; Mathews, 2017; Vlase & Preoteasa, 2021), or the overall experience of camming (Jones, 2020; Nayar, 2017; Stuart, 2022). However, ranking systems can vary significantly, calling for studies that compare them across multiple platforms.…”
Section: Introductionmentioning
confidence: 99%